The Influence of Online Marketing Factors and Technology Adoption Factors on Acceptance of Payment Services via the “True Money Wallet” Application of Subscribers in Bangkok - Suksrichavalit, Kiattisak; Intuluck, Watit (Dusit Thani College Journal, 2020)
This research aims to study factors affecting the acceptance of payment services via the application “True Money Wallet” as perceived by users in Bangkok. It is classified according to demographic factors and social media marketing and the technology adoption factors which Influence the acceptance of the use of payment services through the application “True Money Wallet” of users in the Bangkok area. The sample is a population aged 15 - 59 years living in Bangkok, consisting of 350 people. This research is quantitative research. Data collection was done by using the developed questionnaire and were analyzed statistics Multiple regression. The research found that the target sample who has different age groups, education levels, occupations and income levels tends to have a level of acceptance of the use of payment services through the application “True Money Wallet” as per the perceptions of service users in Bangkok differently with a statistic significance of 0.05 and when studying social media marketing and the technology adoption factors Influence the level of acceptance of the use of payment services through the application “True Money Wallet” of users in Bangkok, the results of the hypothesis testing found that the social media marketing factors and technology acceptance factors can together explain the acceptance of the use of payment services through the application “True Money Wallet” by 46.3% (Adjust R2 = .463) and when controlling the influence of other independent variables, there are 2 independent variables that influenced the acceptance of payment services via the application “True Money Wallet”, such as Electronic Word of Mouth (EWOM) and awareness of the benefits with a statistical significance of 0.05